2015
DOI: 10.1111/ijsa.12117
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of Cognitive and Noncognitive Validities across Personality‐based Job Families

Abstract: The positive relationship between complexity of work and the validity of general mental ability (GMA) measures across a variety of occupations is well supported by research and provides important practical and theoretical support for cognitive ability measures. However, there is currently no research demonstrating a systematic relationship between the size of the validities of any personality measure and the personality requirements of jobs, thus leaving open to question the predictive and construct validity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 73 publications
(118 reference statements)
0
5
0
Order By: Relevance
“…Recent research has demonstrated that focusing on situational demands results in better understanding of crosssituational functionality of empirically keyed biodata. MacLane & Cucina (2015) found that criterion-keying biodata in jobs that required social competence was highly predictive of performance in other jobs that required interpersonal effectiveness but not as predictive for jobs less demanding. Personality psychologists may also find benefits from contextualizing questionnaires that ask about past biographical data.…”
Section: Additional Opportunities For Contextualizationmentioning
confidence: 91%
“…Recent research has demonstrated that focusing on situational demands results in better understanding of crosssituational functionality of empirically keyed biodata. MacLane & Cucina (2015) found that criterion-keying biodata in jobs that required social competence was highly predictive of performance in other jobs that required interpersonal effectiveness but not as predictive for jobs less demanding. Personality psychologists may also find benefits from contextualizing questionnaires that ask about past biographical data.…”
Section: Additional Opportunities For Contextualizationmentioning
confidence: 91%
“…Within the biodata literature, published research has generally not focused on how situational job features affect biodata key generalization to other samples or different criteria. Although a few studies have explicitly addressed the impact of situational features on empirically keyed biodata validity (Carlson et al, ; Gandy, Dye, & MacLane, ; MacLane & Cucina, ; Rothstein et al, ), there are differences in how situational factors were conceptualized, and the lack of a unified framework have prevented a concrete understanding of how contextual factors affect the development of biodata keys.…”
Section: Impact Of Contextual Features On Empirically Scoring Of Biodmentioning
confidence: 99%
“…Biodata studies that have examined the impacts of contextual factors on empirical biodata keying have taken somewhat diverse approaches. For example, MacLane and Cucina () keyed biodata items upon a specific behavioral criterion (social competence) and within a context where that behavioral domain was highly valued. They then showed that correlations between the scores on the biodata inventory and interpersonal performance were stronger in job families, where socially competent behavior was more important.…”
Section: Impact Of Contextual Features On Empirically Scoring Of Biodmentioning
confidence: 99%
See 2 more Smart Citations